Agricultura familiar e relações de gênero: mapeando a região sul do Brasil - Bueno, Caroline Tapia (2023)
Family farming is surrounded by inequalities, especially in Southern Brazil. Processes of gender inequalities are frequent and have a direct impact on rural relations, such as the preference for men in the succession and inheritance process, the assumption that female work is help, the lack of recognition of domestic work, among other issues highlighted by Brumer (2004) and Paulilo (2016). Considering the importance of family farming, it is essential to understand the dynamics that take place in this sector and the subjects that are part of it. This research aims to contribute to feminist geographic science. In addition to highlighting the inequalities experienced in rural areas, through mapping based on agricultural censuses, it focuses on disseminating this knowledge in a didactic and easily accessible way, seeking to deconstruct thoughts and a critical view of gender inequalities experienced in the countryside, with an emphasis on family farming in southern Brazil. Our thesis is that processes of gender inequality, which place rural women in inferior situations to men, are based on a patriarchal structure that can be mapped using agricultural censuses and denounced both by academic and social movements. By making these inequalities visible, we aim to contribute to the disruption of this system. The general objective is to identify inequalities between genders in the logic of family farming and link such factors to the spatial organization of family farming in southern Brazil. The research consisted of five main stages: bibliographical research, data collection, construction of cartographic products, analysis of results, and six interviews with different women leaders of organizations about the situation of women in the countryside. The stages were constructed and reconstructed simultaneously throughout the research period. The section used in the study is composed of the mesoregions: Northwest Rio Grande do Sul, West Santa Catarina, and West Paraná. Thematic cartography was used as a tool to discuss the research problem. Numerous situations were discussed and made it possible to observe gender inequalities. We looked at the number of establishments with female management, area, heritage, employability, and in none of these categories women outnumbered men. It was observed that the historical burden of patriarchy, even in a different and subtle way, is still present. Thus, it was possible to conclude that patriarchy is not extinct, but embedded in the social relations of family farming, which could be seen and portrayed in the maps and graphs.